The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/oalib.1100804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training and Motivation on Job Performance of Library Personnel of University of Lagos, Lagos State, Nigeria

Abstract: The study investigated the effect of training and motivation on job performance of library personnel of University of Lagos, Lagos State, Nigeria. Observation show that library users frequently complain that library staff do not attend to their queries properly. This phenomenon could be attributed to lack of training and motivation to the library personnel. Survey method was used in the study. The population comprised 135 library personnel in the University of Lagos. Total enumeration was employed as sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Similarly, Madukoma, Akpa, and Okafor (2014) attest training motivates library personnel in University of Lagos to do their jobs. This relationship was found with statistically significant effect on overall organizational performance [28]. However, Zwick (2015) relate effectiveness of training with its content than the duration, financing and initiative, He state the main reason for the differences in training effectiveness during the life cycle is that firms do not take into account differences in training motivation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Madukoma, Akpa, and Okafor (2014) attest training motivates library personnel in University of Lagos to do their jobs. This relationship was found with statistically significant effect on overall organizational performance [28]. However, Zwick (2015) relate effectiveness of training with its content than the duration, financing and initiative, He state the main reason for the differences in training effectiveness during the life cycle is that firms do not take into account differences in training motivation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Extracted information showed that the factor of active leadership in librarianship played a positive role in motivating library professionals toward professional development-related activities on a practical basis. Different studies showed that leadership traits of librarians (Walter, 2006), problem-solving groups (Anyaegbu and Wali, 2020), Buddy system (Anyaegbu and Wali, 2020), coaching and mentorship (Anyim, 2021), teamwork (Issa, 2021), staff relations (Cobblah and van der Walt, 2017), good communication climates (Madukoma et al, 2014), and mentorship and peer coaching (Pan and Hovde, 2010). These different traits of dynamic library leadership played a significant part in the cognitive enhancement of library professionals to motivate them to develop required professional skills to serve the community through smart library devices.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Results revealed that significant studies were related to the factor of IT that led library professionals toward PD programs (Anyaegbu and Wali, 2020; Auster and Chan, 2004; Chan and Auster, 2005; Cobblah and van der Walt, 2017; Cossham and Fields, 2006; Imam et al, 2021; Issa, 2021; Jiang and Zhang, 2011; Pan and Hovde, 2010; Stephen and Oghenekaro, 2020). Active leadership was also effective to motivate library staff toward professional development in the best interests of the organizations according to several studies conducted by authors belonging to different regions of the world (Walter, 2006), problem-solving groups (Anyaegbu and Wali, 2020), Buddy system (Anyaegbu and Wali, 2020; Anyim, 2021; Cobblah and van der Walt, 2017; Issa, 2021; Madukoma et al, 2014). Professional associations of the library played a good role in conducting activities to build professional development of the library professionals and these associations and organizations also created a good image of librarianship in the society (Auster and Chan, 2004; Cobblah and van der Walt, 2017; Pan and Hovde, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lutwama et al (2013) mentioned that, it has not been established as to which type of rewards, in particular, has the most effective impact on people's reactions and performance. The effect of compensation on human capital performance is in most occasions expressively misconstrued and the harmonization of reward classifications reinforces the achievement of competitiveness (Madukoma et al 2014). Madhura and Deepika (2014) stated that, the best way to ensure the continued viability of government institutions amidst perplexing economic environs is to lay emphasis on reward management and institutional performance.…”
Section: Reward and Retention Of High-level Performersmentioning
confidence: 99%